USING THE GEOMETRIC SIMULATION AT PLANNING OF MIXERS OF TELESCOPIC CONSTRUCTION - Miroshnychenko, K. K. (Science and Transport Progress, 2015)
Purpose. The use of traditional processing methods to obtain a homogeneous fiber reinforced concrete does not ensure the creation of high quality, homogeneous construction materials. This study aimes to develop (with the use of geometric simulation of different variants of the working parts of faucets, ensures effective mixing of building structures from concrete. Methodology. The complex of theoretical research allowed formulating the design principles of resource-saving technologies of production of particulate-reinforced compounds with high performance properties. Using the geometric simulation developed different versions of the blades of the working bodies of mixers with the complex geometric shapes, providing excellent mixing of the the fiber-reinforced fine-grained material. Findings. As a result of theoretical and experimental studies aimed at developing the fundamentally new approaches to the preparation (mixing) of fiber-reinforced concrete with different types of fibers and the manufacture of products from them, the author obtained some results. Namely the technology of preparation of fiber-reinforced concrete using telescopic design mixers with effective blades of complex shape was developed. Application of the developed blades allows obtaining a homogeneous fiber-reinforced concrete composition. Due to the high quality of mixing the time of preparation of the mixture reduces. This factor reduces the repair costs of equipment and electricity. Originality. The author developed the design of the mixer with the working body of the telescopic type with blades of complex shape. Practical value. The use of the proposed technology of mixing a particle-reinforced material with the use of the mixer with a working body of a telescopic design with blades with complex geometric shapes provides the high uniformity of fiber-reinforced concrete composition. The author proposed technological methods of production, allow expanding the scope of fibroareolar fine-grained concrete significantly.